“I only knew how to search Google”: students’ reflections on a four-year information literacy curriculum - Stephanie Sanger; Denise A Smith (Journal of the Canadian Health Libraries Association)
Introduction: For undergraduate general health sciences education, there is insufficient high-quality evidence that speaks to the benefits and challenges of an integrated and scaffolded information literacy (IL) curriculum when compared to more traditional modes of delivery. Calls for scaffolded and curriculum-integrated programs are on the rise.